2003
DOI: 10.2337/diabetes.52.3.846
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Antioxidant Genes to Hyperglycemia Is Abnormal in Patients With Type 1 Diabetes and Diabetic Nephropathy

Abstract: Increased flux of glucose through the polyol pathway may cause generation of excess reactive oxygen species (ROS), leading to tissue damage. Abnormalities in expression of enzymes that protect against oxidant damage may accentuate the oxidative injury. The expression of catalase (CAT), CuZn superoxide-dismutase (CuZn-SOD), glutathione peroxidase (GPX), and Mn superoxide-dismutase (MnSOD) mRNA was quantified in peripheral blood mononuclear cells-obtained from 26 patients with type 1 diabetes and nephropathy, 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(76 citation statements)
references
References 46 publications
9
62
0
2
Order By: Relevance
“…Moreover, catalase is one of 20 susceptible genes in type 1 diabetic patients with nephropathy (48). Patients with nephropathy showed a lower expression of catalase when compared with those without complications (49). In line with these observations, in this study, we found that high glucose decreased the expression of both catalase mRNA and protein in renal mesangial cells (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, catalase is one of 20 susceptible genes in type 1 diabetic patients with nephropathy (48). Patients with nephropathy showed a lower expression of catalase when compared with those without complications (49). In line with these observations, in this study, we found that high glucose decreased the expression of both catalase mRNA and protein in renal mesangial cells (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, in T1DM patients with nephropathy, SOD is less up-regulated than in patients without nephropathy, again suggesting that SOD plays an important role in the susceptibility to develop diabetic complications (28).…”
Section: Endothelium and Sod In Diabetic Childrenmentioning
confidence: 99%
“…Evidence suggests that glucose alters antioxidant defences in endothelial cells and in patients with diabetic complications such as DN (Ceriello et al 2000;Hodgkinson et al 2003). Fibroblasts derived from type 1 diabetic patients susceptible to microvascular complications were unable to upregulate their protective antioxidative defences after exposure to high glucose compared with skin fibroblasts from normal subjects, suggesting a failure of antioxidant defences in diabetic patients with nephropathy .…”
Section: A Role For Antioxidant Defence In Diabetic Complicationsmentioning
confidence: 88%